Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, x^2 + 2xy + y^2 - x - y - 12
= (x^2 + 2xy + y^2) - (x + y) - 16 + 4
= (x + y)^2 - 4^2 - (x + y - 4)
= (x + y - 4)(x + y + 4) - (x + y - 4)
= (x + y - 4)(x + y + 4 - 1)
= (x + y - 4)(x + y + 3)
b, x^6 + 27
= (x^2)^3 + 3^3
= (x^2 + 3)[(x^2)^2 - 3x^2 + 3^2]
= (x^2 + 3)(x^4 - 3x^2 + 9)
c, x^7 + x^5 + 1
=x^7 - x^6 + x^5 - x^3 + x^2 + x^6 - x^5 + x^4 - x^2 + x + x^5 - x^4 + x^3 - x + 1
= (x^2 + x + 1)(x^5 - x^4 + x^3 - x+1)
a) => 4x2y2 - (4x2.2) yz + 4x2z2
=> 4x2.(y2+yz+z2 - 2)
chắc sai!! 45454655474675675685685787686845765756856876
a) \(4x^2y^2-8x^2yz+4x^2z^2\)
\(=\left(2xy\right)^2-2.2xy.2xz+\left(2xz\right)^2\)
\(=\left(2xy-2xz\right)^2\)
\(=4x^2\left(y-z\right)^2\)
b) \(x^8+x^7+x^6+x^5+x^3\)
\(=x^3\left(x^5+x^4+x^3+x^2+1\right)\)( có lẽ vậy )
Ta có:
\(x^9-x^7-x^6-x^5+x^4+x^3+x^2-1\)
\(=\left(x^9-x^8\right)+\left(x^8-x^7\right)-\left(x^6-x^5\right)-\left(2x^5-2x^4\right)-\left(x^4-x^3\right)+\left(x^2-x\right)+\left(x-1\right) \)
\(=x^8.\left(x-1\right)+x^7.\left(x-1\right)-x^5.\left(x-1\right)-2x^4.\left(x-1\right)-x^3\left(x-1\right)+x\left(x-1\right)+\left(x-1\right)\)
\(=\left(x-1\right)\left(x^8+x^7-x^5-2x^4-x^3+x+1\right)\)
\(\left(x^2+x\right)^2-\left(x^2+x\right)-6=x^4+2x^3+x^2-x^2-x-6\)
\(=x^4+2x^3-x-6\)
\(=x^4+x^3+2x^2+x^3 +x^2+2x-3x^2-3x-6\)
\(=\left(x^4+x^3+2x^2\right)+\left(x^3+x^2+2x\right)-\left(3x^2+3x+6\right)\)
\(=x^2\left(x^2+x+2\right)+x\left(x^2+x+2\right)-3\left(x^2+x+2\right)\)
\(=\left(x^2+x+2\right)\left(x^2+x-3\right)\)
a) \(x^6-y^6=\text{(x-y)(y+x)(y^2-xy+x^2)(y^2+xy+x^2)}\) b)\(x^2+x+\frac{1}{4}=\left(x+\frac{1}{2}\right)^2\)
x6+x4+x2y2+y4-y6=(x6-y6)+(x4+x2y2+y4)=(x2-y2)(x4+x2y2+y4)+(x4+x2y2+y4)=(x4+x2y2+y4)(x2-y2+1)=((x2+y2)2-x2y2)(x2-y2+1)
=(x2+xy+y2)(x2-xy+y2)(x2-y2+1)
x4-30x2+31x-30=(x4+x)-(30x2-30x+30)=x(x+1)(x2-x+1)-30(x2-x+1)=(x2-x+1)(x2+x-30)=(x2-x+1)(x-5)(x+6)
\(x^5+x^4+2\)
\(=x^5+x^4+x^2-x^2+1+1\)
\(=\left(x^5-x^2\right)+\left(x^4+x^2+1\right)\)
\(=\left(x^5-x^2\right)+\left(x^4+2x^2-x^2+1\right)+1\)
\(=x^2\left(x^3-1\right)+\left(x^4+2x^2-x^2+1\right)+1\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(\left(x^2+1\right)^2-x^2\right)+1\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+1+x\right)\cdot\left(x^2+1-x\right)+1\)
\(=\left(x^3-x^2\right)\left(x^2+x+1\right)+\left(x^2+1+x\right)\cdot\left(x^2+1-x\right)+1\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+x^2+1-x\right)+1\)
\(=\left(x^2+x+1\right)\left(x^3+1-x\right)+1\)
x 2 + 5 x – 6 = x 2 – x + 6 x – 6 = ( x 2 – x ) + 6( x – 1)
= x ( x – 1) + 6( x – 1) = ( x – 1)( x + 6)